Modalitas Elite Lokal Dan Restrukturisasi Koalisi: Studi Longitudinal Dinamika Pilkada Jeneponto 2013–2024 - andrew kresna; Isman Triyadi Iskan (STISIPOL Raja Haji, 2026)
This study analyzes the influence of local elite modalities, economic, social, cultural, and symbolic, in the formation and restructuring of coalitions in Jeneponto Regional Elections through a longitudinal perspective spanning 2013–2024. Using a qualitative case study approach with secondary data analysis, the research traces the evolution of coalitionmechanisms from the 2013 Regional Election (dominant symbolic capital, 51.04%) to 2018 (complete modal integration, 42.98% vote share but 52.4% electability) and contextualizes these findings with contemporary dynamics. While prior studies have separately examined pragmatic coalitions, political dynasties, and Bourdieu's capital in Indonesian local politics, they have rarely traced how the configuration of elite modalities transforms within a singlelocality across multiple electoral cycles. Addressing this gap, the study's novelty lies in constructing a longitudinal analytical framework that integrates Unified Elite Theory and New Elite Theory with Bourdieu's concept of modalities to explain coalition restructuring in a patrimonial context. Historical findings reveal the fragmentation of the Iksan–Mulyadi coalition and substitution with Paris Yasir as an optimization of modal combination, while contextualization with recent literature shows this pattern remains relevant in the 2024 elections, where political dynasties increasingly rely on material- and network-based mechanisms. Methodologically, the framework links historical findings to contemporary issues of oligarchy and political dynasties, illuminating long-term trajectories of local coalitiontransformation. Practically, the research provides insights into coalition restructuring mechanisms and elite modal shifts useful for anticipating future regional election dynamics and designing more equitable electoral reforms.